Ethnic Stereotypes and English As a Foreign Language Learning - Mihaljević Djigunović, Jelena (Array, 1998)
The article investigates relations between learners' attitudes towads the native speakers of English and learner achivement in English as a foreign language.Stereotypes that Croatian teenage EFL learners have about the British and Americans are looked into and in the conclusion, it is stressed that, while attitudes towards the native speakers may be decisive for ESL learners' achievement, other kinds of attitudes are more relevant in EFL context.